Design of robust Hoo, fuzzy and LQR controller for active suspension of a quarter car model - Mohammed, Kaleemullah; Faris, Waleed Fekry; Faried, Hasbullah (2011)
In this paper design of active suspension in a quarter car model is presented. The idea of suspension is to improve the ride quality while maintaining good handling characteristics to different road disturbance. The purpose of designing the active controller for vehicle suspension systems is to decrease the traditional design between ride and handling by directly controlling the suspension forces to suit the road and driving conditions. The presented approach uses linear controller that does not require physical model of shock absorber or the car which is time consuming to derive and implement. Performance of active suspensions like robust Hoo controller, LQR controller and Fuzzy control are compared with existing passive suspension. Simulation result shows that the active controllers are better than passive in terms of settling time.